Determinación del efecto de aceites esenciales en comparación con un promotor de crecimiento en cerdos - Ocampo Rivera, Edwin Alexander (2025)
Weaning is a critical phase in swine production, during which piglets are highly vulnerable due to the physiological, immunological, and nutritional changes associated with the transition to solid feed intake. In this context, the present study aimed to evaluate the effect of a blend of essential oils compared to a conventional growth promoter on productive and physiological parameters in weaned piglets. A total of 21 piglets were randomly assigned to three treatment groups (n = 7 per group): T0 (negative control), T1 (a blend of 31 essential oils at 500 mg/kg of feed), and T2 (growth-promoting antibiotic: Bambermycin at 20 ppm). The respective additives were incorporated directly into the balanced diet. Productive performance variables—including body weight, weight gain, feed intake, and feed conversion ratio—were monitored weekly. Additionally, volatile compounds were analyzed via gas chromatography–mass spectrometry (GC-MS), and fecal score, apparent protein digestibility, and the benefit–cost ratio (B/C) were assessed. Results demonstrated that T1 achieved the best productive performance, with a total weight gain of 26,75 kg and a feed conversion ratio of 1,58. GC-MS analysis identified D-limonene (19,98% of peak area) and β-himachalene (11,78%) as the major bioactive components in the essential oil blend. Regarding apparent protein digestibility, the highest value was observed in the control group (T0: 78,55%), followed by T2 (77,44%) and T1 (77,06%). Economically, T1 yielded the highest profitability, with a B/C ratio of 1,15—equivalent to a net return of $0,15 per dollar invested. In conclusion, dietary supplementation with a blend of 31 essential oils appears to be a viable and effective alternative to antibiotic growth promoters, enhancing both the productive and health performance of weaned piglets and potentially contributing to a reduction in the indiscriminate use of antibiotics during this vulnerable stage.